Carbon Dioxide Insufflation Increases Colonoscopic Adenoma Detection Rate Compared With Air Insufflation. Issue 10 (November 2018) - Mills, Christopher D.; McCamley, Chere; Swan, Michael P.
Abstract : Goals: To determine the effect of carbon dioxide insufflation on the most important outcome measure of colonoscopic quality: adenoma detection rate (ADR). Background: Bowel cancer is the second most common cause of cancer deaths in males and females in Australia. Carbon dioxide has in recent times become the insufflation methodology of choice for screening colonoscopy for bowel cancer, as this has been shown to have significant advantages when compared with traditional air insufflation. Study: Endoscopies performed over a period of 9 months immediately before and after the implementation of carbon dioxide insufflation at endoscopy centers were eligible for inclusion. Results: The difference in ADR between the carbon dioxide and air insufflation methods was statistically significant, with an increased ADR in the carbon dioxide group. The superiority of carbon dioxide insufflation was sustained with a logistic regression model, which showed ADR was significantly impacted by insufflation method. Conclusions: Carbon dioxide insufflation is known to reduce abdominal pain, postprocedural duration of abdominal pain, abdominal distension, and analgesic requirements. This study represents for the first time the beneficial effect of carbon dioxide insufflation upon the key quality colonoscopy indicator of ADR.